Oxine based unsymmetrical (O−, N, S/Se) pincer ligands and their palladium(ii) complexes: synthesis, structural aspects and applications as a catalyst in amine and copper-free Sonogashira coupling. (13th March 2017) - Kumar, Satyendra; Saleem, Fariha; Mishra, Manish Kumar; Singh, Ajai K.
Abstract : Newly synthesized and characterized (single crystal structure) complexes, [Pd(O −, N, S/Se)Cl], efficiently catalyse Sonogashira coupling of ArX at 0.5–1 mol%. Abstract : Unsymmetrical pincer ligands having an 8-hydroxyquinoline (oxine) core viz. 2-(phenylthio/selenomethyl) quinolin-8-ol (L1 /L2 ), 2-( N, N -dimethylthiocarbamoyl) quinolin-8-ol (L3 ) and 2-(pyrrolidin-1-ylthiocarbamoyl) quinolin-8-ol (L4 ) were synthesized. 2-Methylquinolin-8-ol was converted to 2-bromomethylquninolin-8-ol, which reacted with PhENa (E = S or Se) to giveL1 andL2, and the Willgerodt–Kindler reaction on an appropriate aldehyde derivative of quinoline gaveL3 andL4 . Upon reaction with Na2 PdCl4 /[Pd(CH3 CN)2 Cl2 ], L1–L4 coordinated as a (O −, N, E) donor (E = S/Se) resulting in complexes [Pd(L –H)Cl] (1–4 ;L =L1–L4 ). The molecular structures ofL1, 1 and2 were established by single crystal X-ray diffraction. The palladium in1 and2 has a nearly square planar geometry. The Pd–S bond distance in1 is 2.2648(14) Å and in2, the Pd–Se bond distance is 2.3641(7) Å. Somewhat rare weak interactions ( viz. C–H⋯Pd and Se⋯Cl) were noticed in the crystals of1 and2, respectively. Complexes1 and2 were found to be efficient in catalyzing Sonogashira coupling under amine and copper free conditions. The catalyst loading of 0.5–1.0 mol% was found to be promising for the conversion of several aryl halides to their coupled products. The yields were lower for ArCl in comparison to ArBr/ArI. The catalytic activity of1 was marginally lower than that of2 . DFT calculations support the catalytic activity order and bond lengths and angles of1 and2 .